Factors Affecting Work Stress in Cleaning Service Workers - Utami, Arvina Putri; Arrazy, Syafran; Susilawati, Susilawati (Indonesian Journal of Global Health Research, 2024)
Work-related stress and depression accounted for 44% of all work-related health prob-lems and 56% of absenteeism from the office due to illness. Some cleaning service re-spondents said that having a lot of work, feeling exhausted, feeling dizzy, personal prob-lems brought to work, and being offended by what colleagues said, allowing them to ex-perience work stress. The purpose of the study was to determine the factors that affect work stress in cleaning service workers at RSUP H. Adam Malik Medan. This study used a cross-sectional design, with the subjects of 115 workers and selected using the starfield random sampling method. The analysis used is the pearson rank correlation test and the one way test. The results showed that there was an influence of age on work stress with a very weak level of influence not unidirectional (p = 0.007, r = -0.248), no influence of sex on work stress (p = 0.037), there was an influence of working period on work stress with a weak level of unidirectional influence (p = 0.015, r = -0.227), no shift influenceWork against work stress (p = 0.273). There is an effect of workload on work stress with very strong and unidirectional influences (p = 0.000, r = 0.951). The conclusion of the research results, factors that affect work stress are age, length of work, and workload, while fac-tors that do not comply with work stress are gender and work shifts.